Welfare State - Andrzej Klimczuk (The Wiley-Blackwell Encyclopedia of Social Theory, 2017)
The welfare state refers to a concept of a state that focuses on ensuring that a broad range of social rights is provided for all citizens by acting on the social mechanisms and consequences of the market economy. In such a state government plays a vital role in balancing social inequalities by providing or subsidizing social benefits and services. This activity is called social policy. Individual countries are characterized by different welfare state models, goals, values, and groups of beneficiaries. Such a state usually supports a recovery from the difficult situation of the population, which is not, itself, able to take care of their basic needs.
Keywords: D69; 300; justice; poverty; social problems; state